(untitled) (Kohesi: Jurnal Sains dan Teknologi, 2025)
This study aims to analyze the influence of security and support service on user emotion in the context of digital platform usage. A quantitative approach was applied by distributing questionnaires to 100 respondents who had used digital platforms in the last three months. The measurement instruments consisted of three variables—security, support service, and emotion—which were tested for validity and reliability. The results of multiple regression analysis showed that both independent variables significantly affected emotion, with an R Square value of 0.314. The significance value of the F-test was 0.000, and the t-tests for each variable also indicated statistically significant influence (p < 0.05). However, the normality tests (Kolmogorov-Smirnov and Shapiro-Wilk) indicated that all variables were not normally distributed. Therefore, alternative non-parametric methods or data transformation could be considered. These findings highlight the importance of enhancing both security and support service features to improve users’ emotional experience when using digital platforms.